The natural products magnetic resonance database (NP-MRD): comprehensive resource for natural products NMR data enabling discovery and understanding - John R. Cort; Jessica L. Bade; Roger G. Linington; Matthew Pin; Ella F. Poynton; Lloyd W. Sumner; James T. Koller; Zachary M. Tretter; Bharat Goel; David S. Wishart; Vasuk Gautam; Scott McKay; et al. (Phytochemistry Letters, 2025)

WASP nest: a worldwide assessment of social Polistine nesting behavior - Sara E. Miller; Sarah E. Bluher; Emily Bell; Alessandro Cini; Rafael Carvalho da Silva; André Rodrigues de Souza; Kristine M. Gandia; Jennifer Jandt; Kevin Loope; Amanda Prato; Jonathan N. Pruitt; David Rankin; et al. (Ecology, 2018)
Cooperative breeding decreases the direct reproductive output of subordinate individuals, but cooperation can be evolutionarily favored when there are challenges or constraints to breeding independently. Environmental factors, including temperature, precipitation, latitude, high seasonality, and environmental harshness have been hypothesized to correlate with the presence of cooperative breeding. However, to test the relationship between cooperation and ecological constraints requires comparative data on the frequency and variation of cooperative breeding across differing environments, ideally replicated across multiple species. Paper wasps are primitively social species, forming colonies composed of reproductively active dominants and foraging subordinates. Adult female wasps, referred to as foundresses, initiate new colonies. Nests can be formed by a single solitary foundress (noncooperative) or by multiple foundress associations (cooperative). Cooperative behavior varies within and among species, making paper wasps species well suited to disentangling ecological correlates of variation in cooperative behavior. This data set reports the frequency and extent of cooperative nest founding for 87 paper wasp species. Data were assembled from more than 170 published sources, previously unpublished field observations, and photographs contributed by citizen scientists to online natural history repositories. The data set includes 25,872 nest observations and reports the cooperative behavioral decisions for 45,297 foundresses. Species names were updated to reflect modern taxonomic revisions. The type of substrate on which the nest was built is also included, when available. A smaller population‐level version of this data set found that the presence or absence of cooperative nesting in paper wasps was correlated with temperature stability and environmental harshness, but these variables did not predict the extent of cooperation within species. This expanded data set contains details about individual nests and further increases the power to address the relationship between the environment and the presence and extent of cooperative breeding. Beyond the ecological drivers of cooperation, these high‐resolution data will be useful for future studies examining the evolutionary consequences of variation in social behavior. This data set may be used for research or educational purposes provided that this data paper is cited.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Variability of Albedo and Utility of the MODIS Albedo Product in Forested Wetlands - David M. Sumner; Qinglong Wu; Chandra S. Pathak (Wetlands, 2011)

Effects of capillarity and microtopography on wetland specific yield - David M. Sumner (Wetlands, 2007)

Alternate corrections for estimating actual wetland evapotranspiration from potential evapotranspiration - W. Barclay Shoemaker; David M. Sumner (Wetlands, 2006)

Methyl jasmonate and yeast elicitor induce differential transcriptional and metabolic re-programming in cell suspension cultures of the model legume Medicago truncatula - Hideyuki Suzuki; M. S. Srinivasa Reddy; Marina Naoumkina; Naveed Aziz; Gregory D. May; David V. Huhman; Lloyd W. Sumner; Jack W. Blount; Pedro Mendes; Richard A. Dixon (Planta, 2005)